A survey of helium isotopes in Icelandic volcanic materials and geothermal fluids using spatial analysis in ArcGIS - Sunna Harðardóttir 1991- (2016)
The distribution of helium isotope ratios (3He/4He) in Icelandic geothermal fluids, volcanic glasses and phyric lavas was investigated. Published data from previous studies were compiled and a data base with all available data constructed. Modifications of primary (i.e., mantle-derived) helium isotope ratios, due to additions of, for example, air-derived helium and radiogenic ingrowth, were evaluated and the data base was filtered accordingly. The geographical information system ArcGIS (ESRI) was used to perform spatial analysis on the filtered data base. An interpolation method called Natural Neighbor was used to calculate representative helium isotope ratios for all parts of Iceland, including off-axis regions. In accordance to prior studies, the results show that helium isotope ratios in the whole of Iceland vary from 5.1 to 37.7 RA (where RA is the 3He/4He ratio of air (Füri et al., 2010)). However, this study allows for a fine-scale distinction to be made between individual rift segments and off-rift regions. The results clearly reveal that each rift zone has its own distinctive isotope signature: 12-17 RA in the Western Rift Zone (WRZ), 8-11 RA in the Northern Rift Zone (NRZ) and 18-21 RA in the Eastern Rift Zone (ERZ). A high helium plateau, characterized by values ≥ 20 RA is located in Central Iceland and covers an area of 85 × 50 km. This plateau continues down the propagating ERZ and through the South Iceland Seismic Zone (SISZ) and coincides with many geological features, e.g., eruption rates, seismic velocity and gravity anomalies. Such high helium isotope ratios have been associated with undegassed and primordial mantle sources that have been isolated in the lower mantle over Earth’s history. The high helium plateau therefore, marks the conduit of the mantle plume underlying central Iceland. Dreifing helíum samsætna var rannsökuð í íslenskum jarðhitavökvum, glerjum og dílóttum hraunum. Útgefnum gögnum frá fyrri rannsóknum var safnað saman og út frá þeim var settur saman gagnagrunnur. Breytingar á ...